2016
DOI: 10.1016/j.apm.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Dual-channel supply chain: A strategy to maximize profit

Abstract: The rapid pace of e-commerce development has resulted in several manufacturers selling their products online to stay competitive and increase accessibility to their products. This paper investigates the effect of adopting a dual-channel (comprised of a traditional retail channel and a direct online channel) on the performance of a two-level supply chain (manufacturer-retailer). Through this strategy, the manufacturer would like to offer customized products through a direct online channel (i.e. make-to-order), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 44 publications
0
61
0
2
Order By: Relevance
“…Another topic that has received significant attention in the literature is the analysis of multilevel supply chain with consignment stores. The result of these researches showed the following advantages of using consignment stores in supply chain [18]: improved customer service through decreased reaction time on customer's demands, levelling of customer's demands, decreased inventory on the side of the supplier [19], and cost reduction [20]. The possible control processes of consignment inventory have been studied in the literature; consignment arrangements from the point of view of suppliers and retailers are discussed [21].…”
Section: Research On Consignment Storesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another topic that has received significant attention in the literature is the analysis of multilevel supply chain with consignment stores. The result of these researches showed the following advantages of using consignment stores in supply chain [18]: improved customer service through decreased reaction time on customer's demands, levelling of customer's demands, decreased inventory on the side of the supplier [19], and cost reduction [20]. The possible control processes of consignment inventory have been studied in the literature; consignment arrangements from the point of view of suppliers and retailers are discussed [21].…”
Section: Research On Consignment Storesmentioning
confidence: 99%
“…There has recently been an Complexity 3 increased interest in performance analysis of supply chains [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and some recent analysis has been targeted specifically towards the integration of consignment stores into supply chain processes [15][16][17][18][19][20][21] and optimization with metaheuristics based on swarming algorithms [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], especially black hole optimization. Firstly, the relevant terms were defined and the initial searches were conducted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It follows from (2) and (3) that the firstand second-order derivatives of 1 to 1 and 2 to 2 can be shown as It follows from (C.3) that is concave in , = 1, 2. Therefore, by setting (C.1) and (C.2) to zero and solving them simultaneously, we obtain (9).…”
Section: Proofs Of Propositionsmentioning
confidence: 99%
“…Yao and Liu [3] showed that introducing an online channel not only generates competitive pricing and payoffs, but also encourages cost effective retails services. Batarfi et al [9] investigated the effect of adopting a dual channel on the performance of a two-level supply chain; their results show that adding a customized-product online channel would increase the profit of the centralized supply chain system. Huang and Swaminathan [10] and Khouja et al [11] studied the optimal pricing strategy when a retailer sells its product though an dual channel.…”
Section: Introductionmentioning
confidence: 99%
“…The supplier's equilibrium profit can be obtained by substituting equation (5), (6) and (7) in equation (1). These are summarized in Proposition1.…”
Section: Introductionmentioning
confidence: 99%